Kebijakan Pendidikan Keagamaan Islam di Indonesia - Oktiya Hayyu Liyandani; Nur Kolis (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2021)
Abstract: Islamic Religious Education in Indonesia has developed since the Dutch colonial era. At that time Islamic education was carried out halaqah between “kyai” and “santri”. In the land of Islamic education institutions are called “pawiyatan”, which contains ki ajar and cantrik. All religious lessons are derived from the study of the yellow book. In the current era of Islamic Religious Education has been recognized as a sub-part of national education, but in public schools Islamic religious education every week is only given 2 hours of lessons, so religious education especially about ethics and morals does not have much effect on the formation of the religious character of students. This research uses a library research approach with data retrieval through investigation of books, literature, notes, and reports related to research problems to be solved. Therefore, this research is only limited to the discussion of Islamic Education Policy in Indonesia. Abstrak: Pendidikan Keagamaan Islam di Indonesia telah berkembang sejak masa kolonial Belanda. Pada masa tersebut pendidikan islam dilaksanakan secara halaqoh antara kyai dan santri. Ditanah jawa lembaga pendidikan islam disebut dengan pawiyatan, yang didalamnya terdapat ki ajar dan cantrik. Semua pelajaran agama bersumber dari kajian kitab kuning. Pada era sekarang Pendidikan Keagamaan Islam telah diakui menjadi sub bagian dari pendidikan nasional, namun di sekolah negeri pendidikan agama Islam setiap minggunya hanya diberikan 2 jam pelajaran, sehingga pendidikan agama terutama tentang etika dan akhlak tidak terlalu berpengaruh terhadap pembentukan karakter religius siswa. Penelitian ini menggunakan pendekatan library research dengan pengambilan data melalui penyelidikan terhadap buku, literatur, catatan maupun laporan yang berhubungan dengan masalah penelitian yang akan dipecahkan. Oleh karena itu, penelitian ini hanya dibatasi pada pembahasan kebijakan pendidikan Islam di Indonesia.